A Survey: Fault Classification Techniques - Chaudhary, Trisha; Malsa, Nitima (International Journal of Computer Sciences and Engineering, 2025)
Transmission lines consume a considerable amount of power. The necessity of power and its dependency has grown exponentially over the years. The void between limited production and tremendous demand has increased the focus on minimizing power losses. For a modern power system, high speed fault clearance is very critical and to achieve this objective various techniques have been developed. This paper presents survey of various techniques used for classification of transmission line faults.